(3CfSGH GdCTQGa hCNHGQges - (3CHh GdMSf CMeO Hf jMji Hf LGHQ Hf OGhO, GdHdGPQj,J (B279 (3g` s
(3ChdgG (B:s
(3hcGf bO HGjY YHO Gdedc hhYOg Gf dg GdeUYH adeG QGg s
(3BNQgG (B:s
(3hMjf GJjc cJGHi aEfg ef Ggd GdSeY hGdWGYg hgh HOjQ GdLeGLe Je eGdLRA GdMGOi YTQ s
(3GdehLhO efg GdLRA GdMGOi YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B267s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B142 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B38 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdJGQjNs